Temporal measures of modern slavery victimisation - Lightowlers, Carly (Criminology & criminal justice, 2024)
This article examines police data to assess the duration for which different groups of victims of modern slavery endured exploitation and the length of time after their exploitation concluded before it was officially recorded. The article proposes that these measures of modern slavery victimisation can provide important insights into temporal dimensions of the problem and how best to intervene. Reference to current numbers of victims ‘rescued’, it is argued, can be misleading given the proportion of belated reports of exploitation. These are more indicative of systemic failures in the provision of statutory services that young and vulnerable people hesitate to call upon in the context of an increasingly hostile immigration environment.